A study of the clinico-demographical profile of different dengue serotypes circulating in a Southern district of West Bengal, India - Sayani Bose; Feradica D Laloo; Partha Pratim Maity; Anirban Bhaduri (Asian Journal of Medical Sciences)
Background: Dengue virus (DENV) which is endemic in many tropical and subtropical areas around the world has four serotypes (DENV1, DENV2, DENV3and DENV4), this viral infection can either cause mild febrile illness Dengue fever or severe, such as Dengue hemorrhagic fever or Dengue Shock Syndrome. The dominant dengue serotypes in a region often change over time and the infecting serotypes are seen to have an impact on the clinical presentation and outcome of the patient.